2015
DOI: 10.1002/qj.2608
|View full text |Cite
|
Sign up to set email alerts
|

Information content on temperature and water vapour from a hyper‐spectral microwave sensor

Abstract: This study examines the information content on atmospheric temperature and humidity profiles that could be provided by a future spaceborne microwave sensor with a few hundred radiances in the millimetre and submillimetre spectral domains (ranging from 7–800 GHz). A channel selection method based on optimal estimation theory is undertaken, using a database of profiles with associated errors from the European Centre for Medium‐Range Weather Forecasts (ECMWF) numerical weather prediction model and the radiative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 50 publications
(85 reference statements)
0
27
0
Order By: Relevance
“…It is common practice to select channels based on information content and/or degrees of freedom for signal Mahfouf et al, 2015;Martinet et al, 2014;Rabier et al, 2002), and this approach has already been used in an oxygen A-band and B-band analysis for aerosol retrievals (Ding et al, 2016).…”
Section: Optimal Estimation and Information Contentmentioning
confidence: 99%
“…It is common practice to select channels based on information content and/or degrees of freedom for signal Mahfouf et al, 2015;Martinet et al, 2014;Rabier et al, 2002), and this approach has already been used in an oxygen A-band and B-band analysis for aerosol retrievals (Ding et al, 2016).…”
Section: Optimal Estimation and Information Contentmentioning
confidence: 99%
“…Maximum impact on the results is provided by the hyper-spectral information on the O2 band around 60 GHz. Mahouf et al [15] found that increasing the number of spectral bands around 55 GHz by a factor of three increases the information content on temperature by a factor of around 1.5. They found a clear benefit, in terms of information content, in increasing the number of spectral channels around the 55 GHz O2 and 183 GHz H2O absorption lines, compared to current and future instruments.…”
Section: Atmospheric Sounding For Numerical Weather Predictionmentioning
confidence: 99%
“…For water vapour retrieval, the AMSU-B/MHS instruments are widely used in satellite data assimilation systems for numerical weather prediction, even though the limited number of spectral channels provides very poor vertical resolution [10][11][12][13]. A recent European Space Agency (ESA) funded study by Prigent et al [14][15][16] compared the predicted retrieval performance of a future hyperspectral microwave instrument to the predicted performance of the microwave (MW) instruments selected to fly on board the next generation of European operational meteorological satellites (MetOp-SG). For clear sky conditions, the reduction in retrieval uncertainty, compared to a priori information, goes from 2% to 10%, depending on the atmospheric layers, and is more than twice as good as what will be achieved with MetOp-SG.…”
Section: Atmospheric Sounding For Numerical Weather Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, also the potential of hyper-spectral sensors in the millimeter/submillimeter wavelength region is explored for clear-sky (Mahfouf et al (2015)) and cloudy-sky (Birman et al (2017)) conditions. Birman et al (2017) find that the information content on hydrometeors can be significantly increased by using a hyper-spectral sensor, but also depends on the assumed microphysical properties of the frozen hydrometeors.…”
mentioning
confidence: 99%